Evaluation of Youth’s Health Risk Behaviors in Baghdad City - Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2016)
Objective(s): To evaluate youth’s health risk behaviors in Baghdad City and to determine the relationship between such behaviors and the youth’s demographic characteristics of age, gender and grade. Methodology: A descriptive study, using the evaluation approach, is carried out to evaluate youth’s health risk behaviors in Baghdad City for the period of January 26th 2016 to May 20th 2016. A non-probability "purposive" sample of (160) University students is selected for the purpose of the study from four groups of colleges (medical, engineering, sciences, and education) and it is equally distributed of (40) student from group of colleges. The sample is consisted of (50%) males and (50%) females. A questionnaire is constructed for the purpose of the study. It is comprised of eight parts which deal with youth’s health risk behaviors of unintentional injuries, tobacco use, drinking alcohol, drug use, sexual behavior, unhealthy dietary behavior, inadequate physical activity, and health related behavior. Internal consistency reliability and content validity are determined for the study instrument through pilot study. Data are collected through the utilization of the questionnaire and the application of the structured interview technique as means of data collection. Data are analyzed through the application of the descriptive statistical data analysis approach which includes frequency, percent, total score and Cronbach alpha correlation coefficient. Results: The study depicts that most of the students have experienced health risk behaviors of unhealthy dietary behavior, inadequate physical activity and health related behavior regardless of their colleges’ classification. Male students have been exposed to health risk behaviors of unintentional injuries, tobacco use, drinking alcohol, drug use and sexual behavior more than female students. Recommendations: The study recommends that Youth Health Risk Behaviors Program should be designed and implemented to present these students with all the information for the prevention and control of such behaviors. Further research is needed to determine whether low grades lead to health risk behaviors or health risk behaviors lead to low grades, or some other factors lead to both of these problems.